Germination and microwave processing of barley (Hordeum vulgare L) changes the structural and physicochemical properties of β-d-glucan & enhances its antioxidant potential. (20th November 2016) - Ahmad, Mudasir; Gani, Adil; Shah, Asima; Gani, Asir; Masoodi, F.A.
Highlights: The barley was employed to germination and microwave processing prior to extraction of β-glucan. The β-glucans were characterized using FTIR, DSC, SEM and Gel permeation chromatography. Antioxidant potential of β-glucans were also analyzed. The processing of barley decreased the Mol. Weight and enhanced antioxidant potential of β-glucan. Abstract: The nutraceutical potential of β-d -glucan is largely dependent on its structure, size and viscosity. The present study analyzed the effect of germination and microwave processing of barley on the structural, size, antioxidant and thermal characteristics of β-d -glucan. The molecular weight and viscosity of β-d -glucan obtained from germinated barley (GGB) were the lowest (144 kDa and 37.33 cp) as compared to β-d -glucan from microwave processed barley (GMB) and unprocessed barley (GUB). The GGB exhibited higher antioxidant potential than GMB and GUB. The Structural elucidation by ATR-FTIR revealed scission in polymeric chain and β glycosydic linkage of β-d -glucan obtained from processed barley. The highest peak intensity at glycosydic linkage in GGB confirms more scission in the molecule. The DSC curve of GGB showed the highest transition temperature. It was concluded that germination of barley can be a good approach for enhancing the antioxidant potential of β-d -glucan.